The The influence of work motivation and work environment on organizational citizenship behavior (ocb) by job satisfaction as an intervening variable (case study of KPP Pratama Medan Polonia) - Budi Alamsyah Siregar (Enrichment : Journal of Management, 2023)
This study aims to determine the effect of work motivation, and work environment on organizational citizenship behavior (OCB) with job satisfaction as an intervening variable. This research was conducted at KPP Pratama Medan Polonia. This research uses associative research statistics with a quantitative approach with SEM PLS (Partial Least Square) chosen as the test tool in this study. The sample of this research is KPP Pratama Medan Polonia employees totaling 100 people. The measurement method used in this study uses a Likert scale. The application used is Partial Least Square (PLS) with the SmartPLS version 3.0 program to present descriptive statistical data. Based on the results of the study, it can be concluded that (1) work motivation has a relevant influence on job satisfaction variables at KPP Pratama Medan Polonia. (2) work environment has a relevant influence on job satisfaction variables at KPP Pratama Medan Polonia. (3) work motivation has an influence on organizational citizenship behavior (OCB) at KPP Pratama Medan Polonia. (4) work environment has an influence on organizational citizenship behavior (OCB) at KPP Pratama Medan Polonia. (5) work motivation has a significant influence on OCB both directly and indirectly by intervening in job satisfaction at KPP Pratama Medan Polonia. (6) work environment has a relevant influence on OCB both directly and indirectly with job satisfaction intervening. (7) job satisfaction has an influence on organizational citizenship behavior (OCB) at KPP Pratama Medan Polonia